A Review of the Reality of Violent Offending and the Administration of Justice - Zgoba, Kristen M. (Criminal justice policy review, 2021)
Policy makers have recently been exploring methods to reduce incarceration. Most current proposals for reducing incarceration exclude people in prison who were convicted of violent crimes. This article considers violence exclusion from criminal justice reform by examining a sample released from New Jersey’s prisons (n = 375). We assess the hidden nature of the violence in the crime through a review of the characteristics behind the criminal label, with particular focus on the displayed aggravation and mitigation. Postrelease outcomes for this sample are compared with a sample released for nonviolent crimes (n = 1,185). Findings reveal people released for violent offenses frequently display mitigation, as opposed to aggravation. Those released for violent crimes are less likely to be rearrested than those released on nonviolence. The degree of severity of the violence itself has no bearing on the risk of rearrest. Accordingly, policy reform for those convicted of violence is considered.